Pergundikan di Pulau Jawa Masa Hindia Belanda 1870 – 1942 - Pawelling Gesang, Zahra Berliani (Socio Historica: Journal of Islamic Social History, 2024)
This experience examines the reality of husbandry on the island of Java. This study seeks to find out the dark history and oppression carried out by Europeans on native women. The sources used in this research are photographs in KITLV, reports on the De Millionen Uit Deli plantation, Staatsblad, articles in the newspaper Algeemen Handelsblad, and a report recorded in the book entitled Cultuur-Adressbook Voor NederlandscheIndie. This research uses historical methods with a mimetic critical approach and feminist theory. This approach is closely related to literature because mimetic criticism is criticism that views literary works as imitation aspects of everyday things. Meanwhile, feminist theory is closely related to the existence of women who demand the same rights as men. Concubinage caused by economic factors began to become rampant and encouraged native women to live with European men at home without marriage. Not only that, concubinage can also be caused by her family selling their daughters to European men to be concubines. The Dutch East Indies government at that time, namely Jan Pieterszoon Coen, had made various efforts to stop the practice of concubinage, but all their efforts ended in vain. The practice of concubinage involving Indigenous women and European men is certainly a dark history in Indonesia. This concubinage ended when women began to dare to speak out, and also with modernization. The nyai also played a role in modernization and producing a new culture called Indic culture. Indic culture involves several things such as eating style, clothing style, and also language